2014
DOI: 10.1017/s143192761401304x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Functionalized Multiwalled Carbon Nanotubes for Use in an Enzymatic Sensor

Abstract: Carbon nanotubes (CNT) have proven to be materials with great potential for the construction of biosensors. Development of fast, simple, and low cost biosensors to follow reactions in bioprocesses, or to detect food contaminants such as toxins, chemical compounds, and microorganisms, is presently an important research topic. This report includes microscopy and spectroscopy to characterize raw and chemically modified multiwall carbon nanotubes (MWCNTs) synthesized by chemical vapor deposition with the intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…To study the conductive behavior of multiwalled carbon nanotubes (CNTs, Graphistrength CW2‐45; Lacq, France) onto the CA, two approaches were performed. In the first approach, CNTs were previously carboxylic acid functionalized as Guadarrama‐Fernández et al 33 reported, then a proportion of 1 mg/mL of CNTs was added to the solution of CA. This hydrogel solution (CA1) was immersed in ethanol at room temperature (24 ± 3°C) for 15 min and washed several times with distilled water to exchange ethanol.…”
Section: Experimental Section/methodsmentioning
confidence: 99%
“…To study the conductive behavior of multiwalled carbon nanotubes (CNTs, Graphistrength CW2‐45; Lacq, France) onto the CA, two approaches were performed. In the first approach, CNTs were previously carboxylic acid functionalized as Guadarrama‐Fernández et al 33 reported, then a proportion of 1 mg/mL of CNTs was added to the solution of CA. This hydrogel solution (CA1) was immersed in ethanol at room temperature (24 ± 3°C) for 15 min and washed several times with distilled water to exchange ethanol.…”
Section: Experimental Section/methodsmentioning
confidence: 99%
“…TEM transmission electron microscopy, SEM scanning electron microscopy, XPS X-ray photoelectron spectroscopy cation as a biosensor, the capacitance of CNT in each step of the functionalization process was determined using cyclic voltammetry. The changes in the capacitance values show that this functionalization process allows having an active enzyme immobilized onto the CNT surface that can be used in the construction of a sensor (Guadarrama-Fernández et al 2014).…”
Section: Applicationsmentioning
confidence: 99%
“…Functionalization of CNTs with different surface groups (e.g., −OH, −COOH, −NH 2 ) has been accomplished using various different methods (e.g., electrochemical oxidation, acid treatment, plasma treatment), which can greatly affect compound adsorption. Adsorption of organic compounds to CNTs occurs by various mechanisms including electrostatic and hydrophobic interactions, hydrogen bonding, and electron-donor–acceptor (π–π) interactions. Oxygenated CNTs decrease the hydrophobic adsorption of compounds but increase the formation of hydrogen bonding due to a higher content of oxygen groups on the CNTs. Oxygenated CNTs also increase the strength of electrostatic attraction between deprotonated acid groups (e.g., −COO – ) and positively charged compounds. Functionalized CNTs have been extensively used to detect different analytes including lectin and gonadotropin. …”
Section: Introductionmentioning
confidence: 99%